Keamanan dan Kualitas Makanan Pendamping ASI (MPASI) Ransum Bencana dengan Teknologi Pengemasan Retort Pouch: Safety and Quality of Complementary Food (MPASI) as Disaster Emergency Rations Using Retort Pouch Packaging Technology - Nasrulloh, Nanang; Fatmawati, Iin; Mochni, Richard Endang Srihari (Universitas Airlangga, 2024)
Background: Natural disaster is frequently causing disruptions to food availability, including complementary food (MPASI) for toddlers. Therefore, innovation in MPASI as disaster emergency rations with long shelf life and safe for consumption is required through retort pouch packaging technology. Objectives: This research aimed to evaluate safety and quality of MPASI using retort pouch technology during different storage periods. Methods: The experiment was carried out using a single-factor Completely Randomized Design (CRD) method. The treatment factor used was storage periods of 7, 14, and 21 days with 2 repetitions. Analysis of nutritional content including moisture, carbohydrate, protein, fat, and ash as well as safety aspects was carried out through total bacteria count test using the pour plate method. The preparation of MPASI included formulating ingredients such as rice, egg, carrot, green onion, and butter, followed by packaging in retort pouches, sealing, and sterilizing at 121.5°C for 15 minutes. The data analysis used was Analysis of Variance (ANOVA) to determine significance among treatments. Results: The results showed that there was no significant effect of the storage periods on the nutritional content of carbohydrates (p-value = 0.272), protein (p-value = 0.730), fat (p-value = 0.748), ash (p-value = 0.848), and moisture (p-value = 0.806). Similarly, there was no significant effect of storage periods on total bacteria count where the value was still in safe limits (<10 colonies/g). Conclusions: Retort pouch packaging showed the potential to increase the shelf life of MPASI as well as maintain safety and quality.